My fake rake - Leigh, Eva (Leigh, Eva. Union of rakes., 2019)
Lady Grace Wyatt is content as a wallflower, focusing on scientific pursuits rather than the complications of society matches. But when a handsome, celebrated naturalist returns from abroad, Grace wishes, for once, to be noticed. Her solution: to “build” the perfect man, who will court her publicly and help her catch his eye. Grace<U+2019>s colleague, anthropologist Sebastian Holloway, is just the blank slate she requires. To further his own research on English society, Sebastian agrees to let Grace transform him from a bespectacled, bookish academic into a dashing<U+2014>albeit fake<U+2014>rake. Between secret lessons on how to be a rogue and exaggerated public flirtations, Grace<U+2019>s feelings for Sebastian grow from friendship into undeniable, inconvenient, real attraction. If only she hadn<U+2019>t asked him to help her marry someone else... Sebastian is in love with brilliant, beautiful Grace, but their bargain is complete, and she desires another. Yet when he<U+2019>s faced with losing her forever, Sebastian will do whatever it takes to tell her the truth, even if it means risking his own future<U+2014>and his heart.